Are Spatial Visualization Abilities Relevant to Virtual Reality? - Chen, Chwen Jen (University ofSouthern Queensland, 2006)
This study aims to investigate the effects of virtual reality (VR)-based learning environment on learners of different spatial visualization abilities. The findings of the aptitude-by treatment interaction study have shown that learners benefit most from the Guided VR mode, irrespective of their spatial visualization abilities. This indicates that the VR-based learning environment is able to serve as a promising medium to accommodate individual differences in terms of this aptitude.